2022
DOI: 10.1039/d2fo00223j
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility and movement of phenolic compounds from tomato (Solanum lycopersicum) during in vitro gastrointestinal digestion and colonic fermentation

Abstract: Tomatoes (Solanum lycopersicum) are of great significance in terms of the worldwide consuming nutritional diets. Large amounts of nutritional compounds such as phenolics, flavonoids, carotenoids, vitamins, and minerals have drawn...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
6
15
1
Order By: Relevance
“…These clearly demonstrated that phenolic compound release was enhanced throughout colonic fermentation, commonly after 8 h of fermentation, consistent with the study of Wang et al [ 77 ]. Condensed tannins can be found in the plant in the form of oligomers as well as polymers of flavanols, which corresponds to extractable tannins as well as non-extractable tannins.…”
Section: Resultssupporting
confidence: 92%
“…These clearly demonstrated that phenolic compound release was enhanced throughout colonic fermentation, commonly after 8 h of fermentation, consistent with the study of Wang et al [ 77 ]. Condensed tannins can be found in the plant in the form of oligomers as well as polymers of flavanols, which corresponds to extractable tannins as well as non-extractable tannins.…”
Section: Resultssupporting
confidence: 92%
“…There may be a reduction in antioxidant power due to the breakdown of bioactive compounds during digestion [ 40 ]. Other studies not limited to Wang et al [ 41 ], however, have reported higher antioxidant power activities in fermented tomato juice after digestion and the differences observed may be due to the different types of phenolic compounds in food substrates. The higher fold decrease in antioxidant power of fermented MJs fractions at the duodenal phase compared to the GF phase could be related to the pH change from acidic to alkaline [ 37 ].…”
Section: Resultsmentioning
confidence: 91%
“…49 Simultaneously, many previous studies proposed that preliminary sample preparation, such as drying, cutting and grinding, may cause the loss of certain types of phenols. 50…”
Section: Resultsmentioning
confidence: 99%
“…49 Simultaneously, many previous studies proposed that preliminary sample preparation, such as drying, cutting and grinding, may cause the loss of certain types of phenols. 50 With respect to diosmin, it only existed in Spirulina after the colonic fermentation stage, from which it could be inferred that the absorption required the action of colonic bacteria. In contrast, Al-Ishaq et al, 51 achieved hydrolyzation of diosmin in the intestine by microbial enzymes such as α-glucosidase and β-glucosidase into its aglycone-type, diosmetin.…”
Section: Food and Function Papermentioning
confidence: 99%